Transgenic Crop Plants Principles and Development - Kole, Chittaranjan; Michler, Charles H.; Abbott, Albert G.; Hall, Timothy C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Development of transgenic crop plants, their utilization for improved agriculture, health, ecology and environment and their socio-political impacts are currently important fields in education, research and industries and also of interest to policy makers, social activists and regulatory and funding agencies. This work prepared with a class-room approach on this multidisciplinary subject will fill an existing gap and meet the requirements of such a broad section of readers. Volume 1 with ten chapters contributed by 31 eminent scientists from nine countries deliberates on the basic concepts, strategies and tools for development of transgenic crop plants, including topics such as: explants used for the generation of transgenic plants, gene transfer methods, organelle transformation, selection and screening strategies, expression and stability of transgenes, silencing undesirable genes, transgene integration, biosynthesis and biotransformation and metabolic engineering of pathways and gene discovery.
Generation and Deployment of Transgenic Crop Plants: An Overview -- Explants Used for the Generation of Transgenic Plants -- Gene Transfer Methods -- Selection and Screening Strategies -- Levels and Stability of Expression of Transgenes -- Silencing as a Tool for Transgenic Crop Improvement -- Transgene Integration, Expression and Stability in Plants: Strategies for Improvements -- Organelle Transformations -- Biosynthesis and Biotransformation -- Metabolic Engineering of Pathways and Gene Discovery.
Keywords: Life sciences; Agriculture; Plant breeding; Life Sciences; Plant Breeding/Biotechnology.; Plant Genetics & Genomics; Agriculture